Pengambilan Keputusan pada Operasional Penta Coffe Sebagai Usaha Kopi Rumahan dengan Sistem Pre-Order - Sari, Nur Indah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the decision-making process at Penta Coffee, a home-based coffee business that operates using a pre-order (PO) system. This system creates a different decision-making dynamic compared to regular coffee shops because the owner must carefully consider production timing, raw material availability, customer orders, and customer satisfaction within a limited timeframe. A qualitative method with an explanatory survey approach was used to understand the owner’s decision-making patterns when facing challenges in managing labor, capital, raw materials, and marketing. The results show that Penta Coffee's owner combines rational and intuitive decision-making styles. Decisions related to capital and raw material procurement tend to be rational, based on demand data, raw material prices, and profit margins. Meanwhile, marketing and customer service decisions rely more on intuition, driven by experience and customer relationships. Major challenges include limited capital, fluctuating raw material prices, uncertainty in daily order volumes, and building customer trust in a pre-order system. The study concludes that the PO system demands high adaptability and rapid decision-making capabilities in daily operations.